Food styling : the art of preparing food for the camera - Custer, Delores (New Jersey : Wiley, 2010)
Food Styling is the first serious book on the subject of food styling for specific media: editorial, advertorial, public relations, marketing, advertising, packaging, and television and film production.
1. Food styling: an overview -- From home economist to food stylist: a history -- The smorgasbord of food styling -- What is food stylings? -- Business ethics: to enhance, stretch, or cheat? -- 2. The medium is everything -- Editorial food styling versus advertising -- Types of media we work in -- 3. Your food styling teammates -- Who hires food stylists? -- Who will you work with? -- 4. You got the job! Now what? -- Setting a schedule and keeping records -- Bidding and budgeting for the job -- 5. Prepping the assignment -- Starting off: the job folder -- How to read recipes, layouts, storyboards, and scripts -- Brainstorming at the preproduction meeting -- Getting it together: gathering food equipment, and props -- Shooting on location: hidden details -- 6. At the shoot -- Arriving and organizing -- Preparing the food for the shoot -- Styling for visual appeal and mouthwatering factor -- Working on the set -- The shot: it's time to shoot the food -- Back to the office: things to do after the shoot -- 7. About photography -- Photographer's role in a food shot -- Evolution of the camera -- Making a food image work -- Finding the camera angle -- 8. The basics of propping -- Prop stylist in action -- Determining the style: getting the right look -- 9. The basics of TV and film production work -- Food styling for television -- Food styling for film -- The cast of charactersin TV and film production -- Shooting: studio versus location -- Money issues: food budget and your fees -- Shooting a storyboard out of sequence -- 10. Food stylist's tools of the trade -- Kit and the set tray -- Food stylist's knife roll -- Other basic equipment: everything and the kitchen sink -- Tools and equipment at the photographer's studio -- Homemade equipment to the rescue -- Contents in bottles, cans, and packages: a wealth of uses -- 11. Working with the food: overcoming challenges -- 12. The business of food styling -- 13. Beyond food styling: expanding your options -- 14. Tips for chefs, caterers, and others who want to style their food -- 15. Reviewing the last fifty (now sixty) years of food styling and photography.
Includes index.
Keywords: PHOTOGRAPHY OF FOOD